Integrasi Perspektif Pendidikan Agama Kristen Mengenai Toxic leadership di Gereja - Vicia Manuela Tanjung; Juliana Hindradjat (Regula Fidei : Jurnal Pendidikan Agama Kristen, 2026)
: Toxic leadership is a form of destructive leadership that negatively affects individual well-being and organizational sustainability, including within church contexts. Leadership marked by manipulation, authoritarianism, and lack of empathy not only disrupts organizational relationships but also harms the spiritual life of congregations and weakens the church’s witness. Previous studies on toxic leadership in churches have largely focused on managerial and psychological perspectives, while the perspective of Christian Religious Education has received limited attention. This study aims to integrate the perspective of CRE in understanding toxic leadership in the church. Using a qualitative literature review approach, this study analyzes leadership literature, academic journals, and theological sources. The findings indicate that CRE should not be understood as a direct technical solution, but as a framework for character formation and ethical reflection that functions preventively and correctively. This perspective emphasizes servant leadership, humility, justice, and accountability as values opposing toxic leadership.